THE CORRELATION BETWEEN STUDENTS’ LISTENING MOTIVATION, VOCABULARY MASTERY AND SPEAKING ABILITY - Abdur Rahman; Akhmad Multazim; Atikasari Husna; Lutfy Fajar Hudayah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
Purpose of this research is to know the correlation between the students’ Listening Motivation, Vocabulary Mastery, and Speaking ability. The methodology used is in correlation design by using a quantitative method.  The data collecting technique is giving the questionnaire, test, and interview. The data analyzing technique used the correlation of product moment formula to measure the variables. The research findings indicate that there is a significant correlation between students listening motivation, vocabulary mastery, and speaking ability. It was proved by the value of ryx was greater than r table. The correlation between X1 - Y (ryx1) has a value is 0.98, the correlation between X2 - Y (ryx2) has a value is 0.99, the correlation between X1 - X2 (rx1x2) has a value is 0.97, and the correlation between X1 - X2 - Y (rx1x2y) has a value is 0.99. It means that have very high reliability.